2009
DOI: 10.1111/j.1574-695x.2009.00552.x
|View full text |Cite
|
Sign up to set email alerts
|

Value of hepatitis E virus detection by cell culture compared with nested PCR and serological studies by IgM and IgG

Abstract: Hepatitis E virus (HEV) is a well-known cause of sporadic acute hepatitis. The contribution of fecal shedding of the virus to its endemic nature is not frequently studied in underdeveloped countries. The aim of the present study was to detect HEV viremia in serum and stool from patients with acute hepatitis by cell culture and by nested reverse transcriptase (RT)-PCR. A further aim was to evaluate different methods used for HEV detection, including culture by use of HPG11 cell line, PCR, immunoglobulin M (IgM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 42 publications
(45 reference statements)
2
6
0
Order By: Relevance
“…In other words, HEV IgG appears shortly after the IgM response, which appears one week to two months after the onset of illness. Similar to our results, in a series of 44 children with acute HEV (con rmed with HEV viremia in serum and stool by cell culture and RT-PCR), only 35 percent of patients tested positive for HEV-IgM in serum and only 3 percent were positive for HEV-IgG [34]. In another study, HEV-RNA was detected in 23 % of patients followed by the detection of speci c HEV-IgM in 17% and HEV-IgG in 13% of patients.…”
Section: Discussionsupporting
confidence: 90%
“…In other words, HEV IgG appears shortly after the IgM response, which appears one week to two months after the onset of illness. Similar to our results, in a series of 44 children with acute HEV (con rmed with HEV viremia in serum and stool by cell culture and RT-PCR), only 35 percent of patients tested positive for HEV-IgM in serum and only 3 percent were positive for HEV-IgG [34]. In another study, HEV-RNA was detected in 23 % of patients followed by the detection of speci c HEV-IgM in 17% and HEV-IgG in 13% of patients.…”
Section: Discussionsupporting
confidence: 90%
“…Since different HEV genotypes determine the differences of their antibody response to corresponding antigens, the detection results from different ELISA kit might present discordance (Chen et al, 2005). Evidences showed that anti-HEV antibodies, developed in various laboratories using synthetic peptides or recombinant proteins derived from different genotypes and/or subtypes of HEV, showed a wide variation in sensitivity in seroprevalence studies (Zaki et al, 2009;Ma et al, 2011). Furthermore, derived from the same genotype and/or subtype of HEV but expressed in different expression system, the antigenicity and epitope displayed significance difference (Chau et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In the setting of outbreaks, IgM anti-HEV has been detected by enzyme immunoassay on more than 90% of patient serum samples obtained within 1–2 months after the onset of illness 17. However, in another study of patients with acute HEV (defined as acute hepatitis with a HEV viraemia in serum and stool by cell culture and PCR), only 35% of patients tested positive for IgM anti-HEV in serum 18. Therefore, beware the possibility of false negative serology results and consider PCR testing where available if clinical suspicion is high.…”
Section: Diagnosismentioning
confidence: 99%